Nettle supplementation improves antioxidant status and modulates inflammatory response by altering lysophosphatidylcholines and enterolactone metabolism in dairy cows - Qian Zhang; Na Ta; Jize Zhang; Xiaozhen Liu; He Ding; Xiaoqing Zhang (Animal Nutrition, 2025)
Nettle is not only a nutrient-rich forage but also possesses the potential to act as a nutritional and physiological regulator. This study investigated the effects of supplementing nettle hay into the total mixed rations (TMR) on milk yield, milk composition, antioxidant capacity, immune function, and plasma metabolome in dairy cows. Twenty multiparous Holstein cows with similar days in milk (102 ± 8 d), milk production (39 ± 3 kg/d), milk fat (3.78 ± 0.55%), and milk protein (3.24 ± 0.28%) were randomly assigned to two dietary treatments: a control group (AH group, n = 10) receiving a TMR with 10.5% alfalfa hay and a nettle group (NH group, n = 10) receiving a TMR with 10.5% nettle hay. The experiment lasted for 80 d, including a 20 d pre-feeding period. Milk yield and overall composition remained consistent across the groups. However, the NH group exhibited a significant decrease in milk aspartic acid (P = 0.025) and a concomitant increase in arginine (P = 0.031). Nettle supplementation significantly reduced blood aspartate aminotransferase levels (P = 0.005) and improved antioxidant status, as evidenced by a higher total antioxidant capacity (P = 0.039) and total superoxide dismutase activity (P = 0.016), along with lower malondialdehyde (P = 0.018). The metabolome analysis identified 1143 differential metabolites using the positive ionization mode and 1253 differential metabolites using the negative ionization mode. KEGG analysis revealed significant enrichment of differential metabolites in arachidonic acid, linoleic acid, and amino acid metabolism pathways. Lysophosphatidylcholines and enterolactone displayed a significant negative correlation with blood aspartate aminotransferase levels (r < −0.5, P < 0.05) and interleukin-6 levels (r < −0.5, P < 0.05). In conclusion, nettle supplementation significantly influenced the immune and antioxidant capacities of dairy cows by altering the blood metabolome profile. Lysophosphatidylcholines and enterolactone are proposed as potential biomarkers for evaluating the physiological and immune effects of nettle supplementation. Further research is warranted to elucidate the specific mechanisms underlying these effects and optimize the feeding regimen for optimal outcomes.